THE LEGACY OF BROKEN BONDS ATTACHMENT DISRUPTION AND MATERNAL VILLAINY IN FLYNN’S SHARP OBJECTS - Sorhie, Kelevinuo; Das, Nigamananda (International Journal of Research -GRANTHAALAYAH, 2025)
This paper psychoanalyses Adora Crellin from Gillian Flynn’s Sharp Objects, exploring how her early experiences of maternal neglect and disrupted attachment shape her predatory caregiving. Based on Bowlby and Ainsworth’s Attachment Theory, the study argues that Adora’s pathological maternal behaviour, characterised by enmeshment, emotional withdrawal, and factitious caregiving, results from an early disrupted attachment bond formed with her mother, Joya. Her mother’s controlling and emotionally unresponsive attitude, coupled with the abusive grooming of Adora, fostered in her a conception of caregiving as conditional and invasive. An insecurely attached Adora repeats Joya’s parenting style on her daughters, guided by her distorted internal working model of child rearing. The paper positions Adora’s maternal actions as a form of intergenerational trauma, where caregiving becomes a strategy to resolve unfulfilled psychological needs. While Attachment Theory provides a potent psychological framework for interpreting her villainy, the paper also acknowledges its limitations in accounting for the sociocultural influences on her psyche. Further study of her narcissistic traits can deepen insight into how maternal violence disguises itself as care. The paper contributes to broader conversations around the representation of toxic motherhood in literature. It also calls for further exploration of the complex psychological mechanisms behind female-perpetrated abuse in contemporary fiction.